HEDONIC VALUE, PENGALAMAN BERBELANJA, TERHADAP MINAT BELI SITUS SHOPEE DENGAN TRUST SEBAGAI VARIABEL INTERVENING - Lakoni, Idham; Hidayati, Arifah (Universitas Prof. Dr. Hazairin SH, 2022)
The proliferation of internet use has created a new phenomenon of consumer behavior,consumer attention has been diverted to online purchases. Increasing confidence in thetechnology and online payment sector is leading to changes in consumer behavior, away fromtraditional methods. This trend has shown that online shopping has a lot of potential as wellas benefits for consumers and businesses around the world. The purpose of this study was toanalyze hedonic value, shopping experience, on the interest in shopping on shopee sites withtrust as an intervening variable in the city of Bengkulu. This research will be conducted bydistributing 100 questionnaires to students in Bengkulu City as respondents who have madetransactions on the site. shopee. The analysis that will be used is quantitative analysistechniques with path analysis methods (path analysis) with processing using SmartPLS.